2019
DOI: 10.3758/s13421-019-00895-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of control processes in temporal and semantic contiguity

Abstract: Atkinson and Shiffrin (1968) argued that performance on any memory task reflects the combined influence of both the fixed structure of the memory system and control processes tailored to the specific task. We investigated the role of control processes in governing the temporal contiguity and semantic contiguity effects in free recall-tendencies to organize recall based on proximity in the study list and pre-existing semantic associations. Subjects studied lists that contained four "clusters", each composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 74 publications
5
27
1
Order By: Relevance
“…Hong et al (2019) found that combining multiple factors that tend to reduce the usefulness of temporal information, such as testing participants on a long list with semantic associations, can eliminate the TCE. Similarly, when Healey and Uitvlugt (2019) modified free recall instructions to ask participants to focus on similarities in meaning between items rather than the order of items during study, they found the TCE was reduced to near zero. In addition, the correlation between the strength of the TCE and overall recall was much smaller in standard lists composed of relatively unrelated words when participants were instructed to focus on semantic similarities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al (2019) found that combining multiple factors that tend to reduce the usefulness of temporal information, such as testing participants on a long list with semantic associations, can eliminate the TCE. Similarly, when Healey and Uitvlugt (2019) modified free recall instructions to ask participants to focus on similarities in meaning between items rather than the order of items during study, they found the TCE was reduced to near zero. In addition, the correlation between the strength of the TCE and overall recall was much smaller in standard lists composed of relatively unrelated words when participants were instructed to focus on semantic similarities.…”
Section: Discussionmentioning
confidence: 99%
“…Retrieved context theory forms the basis of a set of models of free recall that provide quantitatively precise accounts of dynamics of memory search (see Healey & Kahana, 2014, 2016; Howard et al, 2015; Howard & Kahana, 2002; Lohnas et al, 2015; Polyn et al, 2009; Sederberg et al, 2008). The theory has been applied to explain many phenomena, including the testing effect (Karpicke et al, 2014), directed forgetting (Sahakyan et al, 2013), retrieval-induced forgetting (Kliegl & Bäuml, 2016), age-related change (Healey & Kahana, 2020; Wahlheim & Huff, 2015), individual differences (Healey et al, 2014; Healey & Uitvlugt, 2019), amnesia (Palombo et al, 2019; Sederberg et al, 2008), and event segmentation (Ezzyat & Davachi, 2014; Sahakyan & Smith, 2014).…”
Section: Memory For Temporal Order As An Emergent Property Of Context...mentioning
confidence: 99%
“…Thus, our results control for encoding differences and provide strong support for the modulation of memory based on the retrieval task one is engaged in. In related work, Healey and Uitvlugt (2019) that also examined how poststudy instructional Representation of Our Computational Memory Model for an Example List Note. While inputs to each item node are provided by the desirability ratings, serial position, temporal and semantic associations create the connections between the item nodes.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, recent findings have suggested that the magnitude of this relation can be modulated by instruction and task context. For example, Healey & Uitvlugt (2019) found that the correlation between temporal factor scores and recall was reduced when word lists contained strong semantic associations, and this relationship was even reversed when participants were instructed to use the semantic associations to guide memory search. Supporting this interpretation, Mundorf et al (2021) found a significant correlation between temporal factor scores and recall levels when participants deliberately studied words for a test, but no correlation was found when encoding was incidental.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that temporal contiguity interacts with the semantic associative dimension (Polyn, Erlikhman, & Kahana, 2011, Howard & Kahana, 2002. For example, encouraging participants to focus on temporal order considerably reduces the amount of semantic clustering in participants' recall, even for lists with strong semantic associations (Healey & Uitvlugt, 2019). Little is known, however, about whether time and space interact.…”
Section: Time and Space Interactmentioning
confidence: 99%